2001
DOI: 10.1128/cdli.8.2.288-292.2001
|View full text |Cite
|
Sign up to set email alerts
|

Placental Cellular Immune Response in Women Infected with Human Parvovirus B19 during Pregnancy

Abstract: Human parvovirus B19 can cause congenital infection with variable morbidity and mortality in the fetus and neonate. Although much information exists on the B19-specific antibody response in pregnant women, little information is available describing the cell-mediated immune (CMI) response at the maternal-fetal interface. The focus of this study was to characterize the CMI response within placentas from women who seroconverted to B19 during their pregnancies and compare it to controls. Immunohistochemical techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 37 publications
1
26
0
2
Order By: Relevance
“…43 The cell-mediated immune response at the maternal-fetal interface also contributes to a variable response to parvovirus B19 in pregnancy. 44 Different antibodies may be present for only a short period of several weeks after parvovirus B19 infection. 45 The presence of B19-specific antibodies directed against conformational VP2 epitopes may play an important role in the molecular mimicry for the generation of AT1-AAs.…”
Section: Discussionmentioning
confidence: 99%
“…43 The cell-mediated immune response at the maternal-fetal interface also contributes to a variable response to parvovirus B19 in pregnancy. 44 Different antibodies may be present for only a short period of several weeks after parvovirus B19 infection. 45 The presence of B19-specific antibodies directed against conformational VP2 epitopes may play an important role in the molecular mimicry for the generation of AT1-AAs.…”
Section: Discussionmentioning
confidence: 99%
“…Trophoblasts are not permissive to the virus but may bind viral capsid via the globoside receptor, hence their role in facilitating transcytosis of virus to the fetal circulation [222]. Both inflammatory [223] and apoptotic [224] aspects have been observed in placental tissues in case of B19 infection, probably contributing to fetal damage. Endothelial placental cells can be productively infected, facilitating the establishment of fetal infection and contributing to placental damage [225].…”
Section: Intrauterine Infection and Fetal Damagementioning
confidence: 99%
“…As well as increased IL6 production, high levels of IFN-ª, TNF-AE and IL8 have been detected in the sera of infants with B19-associated acute myocarditis (Nigro et al, 2000). IL2 production at the maternal-fetal interface in women who seroconverted to B19 during pregnancy is thought to determine the outcome of the pregnancy, with high levels of IL2 on the fetal side being associated with pregnancies that result in a poor outcome (Jordan et al, 2001). Ballou et al (2003) have shown recently that a recombinant vaccine (MEDI-491; Medimmune) that is comprised of B19 VP1 and VP2 capsid proteins could elicit neutralizing antibody titres in volunteer adults (n ¼ 24).…”
Section: Cell-mediated Immunitymentioning
confidence: 99%